The Lachnospiraceae-butyric acid axis and its role in glucocorticoid-associated osteonecrosis - Mingbin Guo; Shuai He; Wei Song; Jianbin Mai; Xinwei Yuan; Yixuan Huang; Hongzhong Xi; Guangquan Sun; Yugen Chen; Bin Du; Xin Liu (Journal of Translational Medicine)
Abstract Glucocorticoids (GCs) are key inducers of osteonecrosis, yet not all patients treated with GCs develop glucocorticoid-associated osteonecrosis (GAON). The factors mediating this relationship are unclear. Studies have shown that gut microbiota and their metabolites influence bone metabolism, but their role in GAON is unclear. This study aimed to explore the connection between GAON and gut microbiota. Through bidirectional Mendelian randomization analysis, we identified 14 gut microbial taxa, including Lachnospiraceae (IVW, P = 0.011), associated with GAON. RNA-seq analysis revealed that GAON differentially expressed genes (DEGs) were enriched for intestinal inflammatory response mechanisms. We then compared patients who developed GAON (17 cases), those who did not (GAnON, 15 cases), and those untreated with GCs (Blank, 15 cases) for gut microbiota composition, short-chain fatty acids (SCFAs), and serum inflammatory factors. Our findings indicated a decrease in Lachnospiraceae abundance (GAON 17.13%, GAnON 12.51%, Blank 24.52%) in GC-treated patients. Serum inflammatory factors (IL-17 A, IL-33, and TNF-α) associated with GAON (59.603 ± 12.147, 89.337 ± 20.714, 42.584 ± 9.185) showed significant differences between Blank (1.446 ± 0.683, 11.534 ± 4.705, 4.682 ± 1.48) and GAnON (25.353 ± 8.181, 32.527 ± 7.352, 12.49 ± 3.217) groups, with a negative correlation between these factors and Lachnospiraceae levels. Butyric acid levels in SCFAs varied among groups (P<0.01) and correlated with Lachnospiraceae and inflammatory factors. Controlled experiments in GAON rats demonstrated butyric acid’s osteoprotective role in GAON development (P<0.01). In conclusion, our study suggests that reduced Lachnospiraceae and butyric acid levels, along with increased inflammation due to GCs use, contribute to GAON. Butyric acid may mediate the effects of Lachnospiraceae and inflammation. Butyrate supplementation could potentially reduce GAON incidence, offering a novel approach for its clinical management.